2012
DOI: 10.1007/s15010-012-0326-6
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in congenital heart disease: a frequent community-acquired complication

Abstract: Half of all cases of IE in patients with CHD occurred in patients with non-corrected native-valve CHD and two-thirds were community-acquired. Streptococcus spp. were the most frequent etiological agents. Patients with prosthetic-valve IE present a worse outcome, especially those requiring surgery. Breakthrough bacteremia, nosocomial IE, and heart failure are independent factors of mortality in patients with CHD presenting IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 34 publications
4
37
1
1
Order By: Relevance
“…In a small study also including children, VSD was the most common underlying pathology in IE related to congenital heart disease 18. This reflects that VSD is a common congenital heart lesion and, also in children, the risk of IE is higher in cyanotic heart disease and in AV-septal defects 12…”
Section: Discussionmentioning
confidence: 99%
“…In a small study also including children, VSD was the most common underlying pathology in IE related to congenital heart disease 18. This reflects that VSD is a common congenital heart lesion and, also in children, the risk of IE is higher in cyanotic heart disease and in AV-septal defects 12…”
Section: Discussionmentioning
confidence: 99%
“…Taking note on the infectious agent of bacterial IE, the most common one is known to be Staphylococcus aureus regardless of patients' age [1][2][3][4][5][10][11][12]. However, pathogen of the endocarditis in this case was identified as Lactococcus lactis subspecies.…”
Section: . . . .Discussionmentioning
confidence: 76%
“…Clinicians should suspect IE and observe his course carefully after hospitalization, when newly occurring fever and heart murmur are noticed, especially in case that the patient is a baby. It is also expected 11 for forensic pathologists that they note Lactococcal IE as a not ignorable infectious disease among infants, they are familiar with the symptom, progress and risk for sudden death of this disease, and they should collect and analyze more cases to develop a strategy for the prevention of this disease.…”
Section: Resultsmentioning
confidence: 99%
“…Ventricular septal defect is usually considered a high-risk defect in both children and adults. 9,11 On the other hand, it has been suggested that IE is related primarily to associated valve disease rather to the septal defect itself.…”
Section: Mulder Endocarditis In Congenital Heart Disease 1397mentioning
confidence: 99%